GAMBARAN KONDISI SANITASI LINGKUNGANDAN PERILAKU SANTRI TERKAIT PENYAKIT SKABIES (STUDI DI PONDOK PESANTREN DARUSSALAM BANYUWANGI) - Yusli Harini; Retno Hestiningsih; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Scabies generally attacks people who live in groups such as in dormitories Darussalam Islamic Boarding School of Banyuwangi found many students had a history of scabies.This study objected to describe the incidence of scabies, environmental sanitation, and behavior of moslem students in Darussalam Islamic Boarding School of Banyuwangi.This research is descriptive research type through cross-sectional approach.The research subjects were moslem students who settled in the dormitory Darussalam Islamic Boarding School of Banyuwangi. Samples taken as many as 102 moslem students using proportional random sampling technique.The results showed thatscabies had attacked 84.3% moslem students, most of the respondents have a good knowledge about scabies disease (48%), positive attitudetowards scabies disease (94.1%), exchanging personal equipments with other students, settled a room with relatively poor sanitary conditions (96.1%), and no evidence of mites in the water bathing pool moslem students. It is advisable to carry out activities to improve knowledge, encouragement to behave clean and healthy living, as well as the improvement of boarding facilities comply with health standards.